Analysis of Junior High School Students’ Learning Obstacles on Polyhedron Material Reviewed from the Pirie–Kieren Theory - Safuan Safuan; Syarifah Fadillah; Dewi Risalah (Journal of Educational Sciences, 2026)
This study is motivated by the low level of junior high school students’ understanding of three-dimensional geometry (solid shapes) and the need for a theoretical framework capable of explaining the dynamics of conceptual development more comprehensively. This research aims to analyze learning obstacles and the growth trajectory of students’ understanding using the Pirie–Kieren theory. The study employed a qualitative approach involving diagnostic tests, clinical interviews, observations, and analyses of student learning artifacts, validated through source triangulation, methodological triangulation, and expert confirmation. The findings show that students’ understanding develops non-linearly, with most students remaining at the Property Noticing level, characterized by difficulties in 2D–3D visualizations, conceptual reasoning, and multimodal coordination. The phenomenon of folding back consistently appears as a mechanism for reconstructing understanding when students encounter representational or conceptual conflicts. The analysis indicates the predominance of representational, epistemological, and didactic obstacles that hinder students’ transition toward formal understanding. In conclusion, the Pirie–Kieren theory effectively maps the development of students’ understanding and reveals the root causes of learning barriers in geometry. The study’s implications highlight the importance of representation-based learning design, reasoning scaffolding, and facilitating productive folding back to support deeper geometric understanding.